ASSESSING WORK PERFORMANCE PROVISIONS FOR PROMOTION OF CIVIL SERVANTS IN THE ERA OF DIGITAL SOCIETY - Febriyanto, Satrio Alif; Dwiliandari, Anggie Fauziah (Natapraja, 2022)
Development of the distribution and information massification has increasingly occurred in a new social system supported by economic expansion, technology, and a global information system network. The high intensity of the use of technology in economic and socio-political activities is a sign of the birth of the era of digital society. As an actor with a significant position in government activities and development, it is appropriate for Civil Servants (PNS) to support the dynamics of developing a digital information society. As a generator of national and regional development, personnel assessment in the bureaucracy must adjust to the needs and demands of communicative-informative actions. The Study of the Relevance of Indicators of Performance Appraisal in The Advancement Provisions of Civil Servants in The Digital Society Era is intended to determine the role of civil servants in the development of digital society with the final result in the form of policy recommendations to optimize the role of civil servants in implementing digital society in the advancement aspect. The research method used is juridical-normative through literature studies and legislation relating to the State Civil Apparatus, employee affairs, and the digital society. Based on the research results, digital literacy is the key to optimizing the quality of bureaucratic resources in the era of the digital information society. Therefore, digital literacy needs to be used as an aspect in assessing the work performance of civil servants to accelerate the development of a digital society.